A fluorescent method for the rapid staining and quantitation of proteins in sodium dodecyl sulfate-polyacrylamide gels - Aragay, A.M.; Diaz, P.; Daban, J.R.
Fluorescence studies carried out in solution indicate that in the presence of the anionic detergent sodium dodecyl sulfate (SDS)proteins are able to bind the noncovalent dye 1-anilinonaphthalene-8-sulfonate (ANS). The interaction of this hydrophobic dye with protein-SDS complexes is probably responsible for the fluorescence of protein bands observed by UV-transillumination of polyacrylamide gels stained with ANS. It is shown that the staining of SDS-polyacrylamide gels with ANS after electrophoresis allows the detection and quantitative estimation of proteins and peptides having different properties. The electrophoretic patterns obtained using ANS are equivalent to those obtained using Coomassie Brilliant Blue R-250. The fluorescent staining method described in this work is simpler and much more rapid than conventional methods using visible dyes.
Keywords: FLUORESCENCE; METHODOLOGY; NONHUMAN; POLYACRYLAMIDE GEL ELECTROPHORESIS; PROTEIN STAINING